2019
DOI: 10.18805/lr-4100
|View full text |Cite
|
Sign up to set email alerts
|

Biological Management of Fusarium Wilt in Chickpea (Cicer Arietinum L.) Caused by Fusarium oxysporum f. sp. ciceris

Abstract: In the present study, the three rhizobacterial strains (CPs3, CBs5 and Pf1) and fungal antagonists (CTs2 and Tv1) were evaluated against Fusarium wilt of chickpea under glasshouse and field conditions. Among all the treatments the strain CPs3 (Pseudomonas chlororaphis) has recorded highest germination (100%) and yield parameters viz., yield of 1194.4 kg/ ha with 13 (Number of pod bearing branches/plant), 32.3 (Pods/plant) and 33.0 g of 100 seeds weight with lowest incidence of wilt at 14.3% with disease reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Diverse studies have conducted the search for sources of resistance to F. oxysporum s. l. (Rana et al, 2023), M. phaseolina (Mirchandani et al, 2023), S. rolfsii (Vishruta and Nath, 2021) and S. sclerotiorum (Mwape et al, 2021a) in genotypes of Cicer spp. ; however, only some genotypes of chickpea resistant to F. oxysporum s. l. (Rana et al, 2023) have been found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diverse studies have conducted the search for sources of resistance to F. oxysporum s. l. (Rana et al, 2023), M. phaseolina (Mirchandani et al, 2023), S. rolfsii (Vishruta and Nath, 2021) and S. sclerotiorum (Mwape et al, 2021a) in genotypes of Cicer spp. ; however, only some genotypes of chickpea resistant to F. oxysporum s. l. (Rana et al, 2023) have been found.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse studies have conducted the search for sources of resistance to F. oxysporum s. l. (Rana et al, 2023), M. phaseolina (Mirchandani et al, 2023), S. rolfsii (Vishruta and Nath, 2021) and S. sclerotiorum (Mwape et al, 2021a) in genotypes of Cicer spp. ; however, only some genotypes of chickpea resistant to F. oxysporum s. l. (Rana et al, 2023) have been found. Therefore, there is a need to continue with the search for sources of resistance to the diverse fungi which originate in the soil that affect the chickpea crop, with the aim of including this resistance to the future chickpea varieties to develop in Mexico.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ISSN 2477-9407 factores, destacando las enfermedades ocasionadas por diversos hongos fitopatógenos (Sankar et al, 2019). Fusarium oxysporum y F. solani son dos hongos que causan enfermedades en semillas y raíz de plantas de garbanzo y están considerados como fitopatógenos de importancia debido a su amplia distribución mundial y a las pérdidas que producen anualmente, dentro de los principales síntomas que ocasionan están las pudriciones y/o necrosis en la semilla o pudrición y/o necrosis de raíz y marchitamiento general que provocan la muerte de las plantas en vivero o campo (Sunkad et al, 2019).…”
Section: Romero-bastidas Et Alunclassified